Reviewing the use of research interviews and qualitative inquiry in urban forestry: Understanding human-tree relationships in the built landscape - Powning, Candace B.; Harper, Richard W.; Bloniarz, David V.; Kahl, Katherine J.; Markowitz, Ezra M. (Urban forestry & urban greening, 2024)
In most urban areas, residents have regularly occurring experiences of the trees around them. They interact with trees based on those experiences, as well as their own personal values, priorities, and identities. Whether those interactions with trees are active or passive (and whether or not they are conscious interactions), it is necessary to understand them in order to gain a more detailed picture of the urban forest. Qualitative research, and interviews specifically, are an important tool for developing this knowledge as they can uncover a deep understanding of an individual’s values, experiences and perspectives; build relationships between researchers, practitioners and community members; and support the inclusion of diverse and nontraditional perspectives in the pursuit of procedural and recognitional justice in urban forestry. In order to understand how and why interview methodology is being used to understand human-tree relationships in the built landscape, we employed PRISMA methodology, multiple screening phases, and NVivo qualitative coding software to identify and analyze 112 manuscripts that employed interviews in their study of human perspectives of, and interactions with, built-landscape urban trees. Findings show that interview methods are a relatively new introduction to urban forestry research, and that they have been primarily utilized to learn about: (1) Civilian perspectives/perceptions, sometimes with regard to diverse groups and those historically underrepresented in urban forestry; (2) Civilian participation/decision-making with regard to activities on their own property and volunteer activities in the community; (3) Urban forest manager and arborist perspectives and decision-making; and (4) Stakeholder collaboration – among government entities, NGOs, businesses and volunteers. Most studies (particularly those based in the Global North) prioritized the perspectives of decision-makers over community members, which highlights the need to find new ways of bringing different voices into urban forestry research and practice.